High-entropy negative thermal expansion luminescent material and preparation method thereof

Through the preparation of high-entropy negative thermal expansion luminescent material (Al0.196Sc0.196In0.196Yb0.196Y0.196Er0.02)2Mo3O12, the problem of the decrease in luminescent efficiency of luminescent materials at high temperatures is solved, and the efficient luminescent performance in high temperature environments is achieved. Suitable for high-end technology fields.

CN119144330AActive Publication Date: 2024-12-17ZHENGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411249740.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-17
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The luminescence efficiency of existing luminescent materials in high-temperature environments has dropped sharply, resulting in limited application in high-power or high-temperature working environments. This is mainly due to the insufficient stiffness of the crystal structure, resulting in frequent non-radiative relaxation processes, which weakens the luminescence efficiency.

Method used

Using high entropy negative thermal expansion luminescent material (Al0.196Sc0.196In0.196Yb0.196Y0.196Er0.02)2Mo3O12, the luminescent material is prepared by selecting suitable raw materials and grinding according to stoichiometric molar ratio, and the negative thermal expansion characteristics of high entropy ceramics are used to avoid luminescent material. heat quenching effect.

Benefits of technology

Overcome the thermal quenching characteristics of luminescent materials within a certain temperature range, achieve the improvement of luminescent intensity at high temperatures, combine good thermal stability and low cost, and is suitable for displays, optical temperature sensing and luminescent conversion layers of solar cells. Applications in other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144330A_ABST
    Figure CN119144330A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermal expansion materials, and discloses a high-entropy negative thermal expansion luminescent material and a preparation method thereof. The molecular formula of the fluorescent powder is (Al < 0.196 > Sc < 0.196 > In < 0.196 > Yb < 0.196 > Y < 0.196 > Er < 0.02 >) 2Mo < 3 > O < 12 >. The preparation method comprises the following steps: selecting an Al source, an Sc source, an In source, a Yb source, a Y source, an Er source and a Mo source as raw materials, weighing according to a stoichiometric molar ratio of Al: Sc: In: Yb: Y: Er: Mo = 0.392: 0.392: 0.392: 0.392: 0.392: 0.04: 3 in the target product (Al < 0.196 > Sc < 0.196 > In < 0.196 > Yb < 0.196 > Y < 0.196 > Er < 0.02 >) 2Mo3O12), grinding and mixing uniformly, directly sintering the obtained mixed powder or sintering after tabletting at the sintering temperature of 1000-1100 DEG C for 5-10 hours, and cooling to room temperature to obtain the target product (Al < 0.196 > Sc < The invention provides a high-entropy negative thermal expansion luminescent material with a molecular formula of (Al < 0.196 > Sc < 0.196 > In < 0.196 > Yb < 0.196 > Y < 0.196 > Er < 0.02 >) 2Mo < 3 > O < 12 >, and the thermal quenching characteristic of the luminescent material is overcome within a certain temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal expansion materials, and in particular relates to a high entropy negative thermal expansion luminescent material and a preparation method thereof. Background Art

[0002] Luminescent materials are widely used in modern applications such as lighting, display, optical temperature sensing, luminescence conversion layers of solar cells, and bio-imaging. However, the inevitable thermal quenching (TQ) of most fluorescent materials seriously restricts their further application in high-power optical devices. Thermal quenching (TQ) is a key problem commonly faced by fluorescent materials in high-temperature environments. It causes the luminescence efficiency of the material to drop sharply with increasing temperature, which greatly limits the application of these materials in high-power or high-temperature working environments, such as LED lighting, high-temperature detectors, and bio-imaging. Therefore, improving the luminescence intensity at high temperatures is a challenging task, which has promoted the exploration and research of thermally quenched luminescent materials.

[0003] There is a significant correlation between the TQ (thermal quenching) phenomenon and the rigidity of the crystal structure. Specifically, when the activator is located in a host material with higher rigidity, its luminescence intensity is significantly better than that in a flexible host. This is because the rigid structure can effectively suppress the occurrence of non-radiative relaxation processes, which are more frequent in flexible hosts, thereby weakening the luminescence efficiency. In this context, negative thermal expansion (NTE) host materials show unique advantages. As the temperature increases, these materials do not expand but shrink instead, and this property enables them to obtain higher structural rigidity during the shrinkage process. This increase in rigidity not only enhances the stability of the material, but also reduces the emission loss that may occur in dopants at high temperatures, thereby protecting the integrity of the luminescence center. Therefore, NTE is regarded as an effective strategy to avoid the occurrence of TQ phenomenon, which opens up new ways to improve the performance of luminescent materials in high temperature environments.

[0004] As a new material design strategy, the high entropy solid solution method has attracted widespread attention from researchers in recent years. When the concept of high entropy was introduced into ceramics, various structures of high entropy ceramics (HECs) such as pyrochlore (or defective fluorite) and perovskite were designed and developed one after another. Compared with single-component ceramics, HECs have excellent thermal stability, adjustable thermal expansion properties, incredible phase stability and low thermal conductivity. At present, the application research of HECs is mainly concentrated in the fields of thermal protection and corrosion protection, and there are few reports on its application in the field of NTE. Among the many high entropy ceramic systems, rock salt-type high entropy oxide ceramics are the earliest discovered and easy to synthesize so far, so they have been studied a lot and formed a relatively complete theoretical system. Compared with other high entropy materials, it also has a serious lattice distortion effect, which leads to its relatively low thermal conductivity. Due to the lattice distortion effect, it has extremely low thermal conductivity and high thermal expansion coefficient, which more effectively exerts the NTE performance of its high entropy materials, thereby avoiding the thermal quenching effect of luminescent materials. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, the present invention aims to provide a high entropy negative thermal expansion luminescent material and a preparation method thereof.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A high entropy negative thermal expansion luminescent material, the molecular formula of which is (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 .

[0007] A method for preparing a high entropy negative thermal expansion luminescent material: selecting Al source, Sc source, In source, Yb source, Y source, Er source, and Mo source as raw materials, and preparing a target product (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The stoichiometric molar ratio of Al: Sc: In: Yb: Y: Er: Mo is 0.392: 0.392: 0.392: 0.392: 0.392: 0.04: 3, and the mixture is weighed, ground and mixed evenly. The obtained mixed powder is directly sintered or sintered after tableting. The sintering temperature is 1000-1100° C., the time is 5-10 h, and the mixture is cooled to room temperature to obtain the target product (Al 0.196 Sc 0.196 In 0.196 Yb0.196 Y 0.196 Er 0.02 )2Mo3O 12 ; Wherein, the Al source is Al2O3 or a precursor material that can be heated and decomposed to obtain Al2O3 at a temperature not higher than the sintering temperature; The Sc source is Sc2O3 or a precursor material that can be heated and decomposed to obtain Sc2O3 at a temperature not higher than the sintering temperature; The In source is In2O3 or a precursor material that can be heated and decomposed to obtain In2O3 at a temperature not higher than the sintering temperature; The Yb source is Yb2O3 or a precursor material that can be heated and decomposed to obtain Yb2O3 at a temperature not higher than the sintering temperature; The Y source is Y2O3 or a precursor material that can be heated and decomposed to obtain Y2O3 at a temperature not higher than the sintering temperature; The Er source is Er2O3 or a precursor material that can be heated and decomposed at a temperature not higher than the sintering temperature to obtain Er2O3; The Mo source is MoO3 or a precursor material that can be heated and decomposed at a temperature not higher than the sintering temperature to obtain MoO3.

[0008] Preferably, the Al source, Sc source, In source, Yb source, Y source, Er source and Mo source are weighed in proportion and ground and mixed evenly, and the obtained mixed powder is first directly pre-sintered or sintered after tableting, and then the pre-sintered product is ground and mixed evenly, and then sintered again after tableting; the pre-sintering temperature is 700-800°C and the time is 5-10h, and the secondary sintering temperature is 1000-1100°C and the time is 5-10h.

[0009] Preferably, when Al source, Sc source, In source, Yb source, Y source, Er source and Mo source are weighed in proportion and ground and mixed evenly, wet grinding is adopted, and ethanol is added during grinding, and the added amount is based on wetting Al source, Sc source, In source, Yb source, Y source, Er source and Mo source.

[0010] Preferably, dry grinding is used when grinding and mixing the pre-sintered product uniformly.

[0011] Preferably, the purity of the Al source, Sc source, In source, Yb source, Y source, Er source, and Mo source is 99-99.99wt%.

[0012] Preferably, all sintering processes are carried out at a heating rate of 3-10°C / min to reach the sintering temperature.

[0013] Preferably, all tablets involved are pressed into cylindrical green embryos with a diameter of 8 to 10 mm and a height of 3 to 6 mm.

[0014] Preferably, for all tableting processes involved, the tableting pressure is 4-10 MPa and the holding time is 2-5 min.

[0015] Beneficial effects: (1) The present invention proposes a molecular formula of (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The high entropy negative thermal expansion luminescent material was prepared and its phase purity, thermal expansion properties and luminescence performance were studied. The results showed that (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 Luminescent materials, which overcome the thermal quenching characteristics of luminescent materials within a certain temperature range; (2) The high-entropy NTE luminescent material of the present invention has good thermal stability, simple preparation process, low cost, and is suitable for industrial production. It is expected to be widely used in high-end technical fields such as displays, optical temperature sensors, and luminescence conversion layers of solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 : Example 1 prepared (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 Rietveld refinement of room temperature XRD data.

[0017] Figure 2 :Comparative Example 1 prepared (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 Room temperature XRD pattern of .

[0018] Figure 3 : Example 1 prepared (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O12 Schematic diagram of the structure.

[0019] Figure 4 : Example 1 prepared (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The curve of relative length changing with temperature.

[0020] Figure 5 :Comparative Example 1 prepared (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 The curve of relative length changing with temperature.

[0021] Figure 6 : Example 1 prepared (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 Temperature-dependent emission spectrum under 980 nm laser excitation (a) and a plot of the normalized emission intensity of the 522 nm green emission band versus temperature (b).

[0022] Figure 7 :Comparative Example 1 prepared (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 Temperature-dependent emission spectrum of the 522 nm green emission band under 980 nm laser excitation (a) and a plot of the normalized emission intensity versus temperature of the 522 nm green emission band (b). DETAILED DESCRIPTION

[0023] The following is a clear and complete description of the technical solution of the present invention in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1 Solid-phase method for preparing high entropy negative thermal expansion luminescent materials (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 : Select analytically pure Al2O3, Sc2O3, In2O3, Yb2O3, Y2O3, Er2O3, and MoO3 as raw materials, and precipitate Al2O3, Sc2O3, In2O3, Yb2O3, Y2O3, Er2O3, and MoO3 according to the target product (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The stoichiometric molar ratio of Al: Sc: In: Yb: Y: Er: Mo = 0.392: 0.392: 0.392: 0.392: 0.392: 0.04: 3 was weighed and mixed, put into an agate mortar, and anhydrous ethanol was added to moisten it (the amount of anhydrous ethanol added was based on the amount of Al2O3, Sc2O3, In2O3, Yb2O3, Y2O3, Er2O3 and MoO3), and ground for 2h. The mixed powder was put into a crucible and heated in a muffle furnace. The temperature was raised to 700°C at a heating rate of 5°C / min, and the mixture was pre-sintered for 10 h at a temperature maintained at that temperature. The mixture was cooled to room temperature in the air. The pre-sintered powder was taken out and dry ground. The ground powder was pressed at a pressure of 10 MPa for 2 min into a cylindrical blank with a diameter of 8 mm and a height of 3 mm. The cylindrical blank was placed in a crucible, and the temperature was raised to 1100°C in a muffle furnace at a heating rate of 5°C / min. The mixture was pre-sintered for 10 h at a temperature maintained at that temperature. The mixture was cooled to room temperature in the air. The block sample (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 .

[0025] Comparative Example 1 (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 The preparation method comprises the following steps: Select analytically pure Al2O3, Sc2O3, In2O3, Yb2O3, Y2O3, Er2O3 and MoO3 as raw materials, and precipitate Al2O3, Sc2O3, In2O3, Yb2O3, Y2O3, Er2O3 and MoO3 according to the target product (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 The stoichiometric molar ratio of Al: Sc: In: Yb: Y: Er: Mo = 0.5: 0.5: 0.5: 0.2: 0.28: 0.02: 3 was weighed and mixed, put into an agate mortar, and moistened with anhydrous ethanol (the amount of anhydrous ethanol added was based on the amount of Al2O3, Sc2O3, In2O3, Yb2O3, Y2O3, Er2O3 and MoO3), and ground for 2h. The obtained mixed powder was put into a crucible and heated in a muffle furnace at 5℃ / m The heating rate of in was raised to 700℃, and the temperature was kept for pre-sintering for 10h. The temperature was naturally cooled to room temperature in the air. The pre-sintered powder was taken out and dry ground. The ground powder was pressed into a cylindrical blank with a diameter of 8mm and a height of 3mm at a pressure of 10Mpa for 2min. The cylindrical blank was placed in a crucible, and the temperature was raised to 1000℃ in a muffle furnace at a heating rate of 5℃ / min. The temperature was kept for calcination for 10h, and the temperature was naturally cooled to room temperature in the air to obtain a block sample (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 .

[0026] Product Characterization and Performance Testing Example 1 Preparation of (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The Rietveld refinement pattern of the room temperature XRD of the sample is as follows: Figure 1 As shown, (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The structure of In2Mo3O 12(PDF:04-017-8004), all belong to the Pbcn space group of the orthorhombic system. The XRD diffraction peaks are independent of each other and have small half-height widths, indicating that the sample has good crystallinity. In addition, Rietveld refinement obtained the room temperature (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The lattice parameters are: a=13.50 Å, b=9.72Å, c=9.82 Å, and the lattice volume V=1288.73Å.

[0027] Comparative Example 1 (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 The room temperature XRD pattern of the sample is shown in Figure 2 The XRD diffraction peaks are independent of each other and have a small half-height width, indicating that the sample has good crystallinity. More importantly, (Al 0.25 Sc 0.25 In 0.2 5Y 0.1 Y 0.14 Er 0.01 )2Mo3O 12 The XRD patterns of Sc2Mo3O 12 The results were in good agreement with the standard card (PDF#73-10), indicating that the target product had been successfully prepared.

[0028] Example 1 Preparation of (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The schematic diagram of the sample structure is shown in Figure 3 As shown, Al 3+ Sc 3+ 、In 3+ , Yb 3+ , Y 3+ , Er 3+ With 6 O 2- The anions together form an octahedron with the cation as the center. 6+ Cation with 4 O 2- Ion composition is Mo 6+The MoO4 tetrahedron and the Al / Sc / In / Yb / Y / ErO6 octahedron are connected by bridging oxygen atoms.

[0029] Example 1 Preparation of (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The curve of the relative length of the sample (i.e., dL / L0, where dL = length after expansion - original length L0, the same below) changing with temperature is shown in Figure 4 . (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 The sample shows negative expansion behavior (-5.87×10 -6 K -1 ). In addition, the inflection point in the thermal expansion curve is due to the presence of trace amounts of crystal water in the sample.

[0030] Comparative Example 1 (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 The curve of the relative length of the sample changing with temperature is shown in Figure 5 . (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 The sample shows near-zero thermal expansion behavior (α l = -0.8 × 10 -6 K -1 ).

[0031] Example 1 Preparation of (Al 0.196 Sc 0.196 In 0.196 Yb 0.196 Y 0.196 Er 0.02 )2Mo3O 12 Temperature-dependent emission spectra of the samples under 980 nm laser excitation ( Figure 6 a). Figure 6 a 522nm green emission band (corresponding to Er 3+ Ionic 2 H 11 / 2 → 4 I 15 / 2 After normalizing the emission intensity, it was found that the intensity increased by about 1.6 times in the range of 300-400K, and the emission intensity increased significantly with further increase in temperature. Overall, the emission intensity increased by about 53.4 times in the range of 300-650K ( Figure 6 b) Overcoming the thermal quenching characteristics of the luminescent material.

[0032] Comparative Example 1 (Al 0.25 Sc 0.25 In 0.25 Yb 0.1 Y 0.14 Er 0.01 )2Mo3O 12 Temperature-dependent emission spectra of the samples under 980 nm laser excitation ( Figure 7 a). Figure 7 a 522nm green emission band (corresponding to Er 3+ Ionic 2 H 11 / 2 → 4 I 15 / 2 ) after normalizing the emission intensity, it was found that in the range of 5~650K, the emission intensity decreased by about 3.7 times ( Figure 7 b).

Claims

1. A high entropy negative thermal expansion luminescent material, characterized in that: Its molecular formula is (Al 0.196 Sc 0.196 In 0.196 Yb 0.19 6Y 0.196 Er 0.02 )2Mo3O 12 .

2. A method for preparing a high entropy negative thermal expansion luminescent material as claimed in claim 1, characterized in that: Select Al source, Sc source, In source, Yb source, Y source, Er source, and Mo source as raw materials, and according to the target product (Al 0.196 Sc 0.196 In 0.196 Yb 0.19 6Y 0.196 Er 0.02 )2Mo3O 12 The stoichiometric molar ratio of Al: Sc: In: Yb: Y: Er: Mo is 0.392: 0.392: 0.392: 0.392: 0.392: 0.04: 3, and the mixture is weighed, ground and mixed evenly. The obtained mixed powder is directly sintered or sintered after tableting. The sintering temperature is 1000-1100° C., the time is 5-10 h, and the mixture is cooled to room temperature to obtain the target product (Al 0.196 Sc 0.196 In 0.196 Yb 0.19 6Y 0.196 Er 0.02 )2Mo3O 12; Wherein, the Al source is Al2O3 or a precursor material that can be heated and decomposed to obtain Al2O3 at a temperature not higher than the sintering temperature; The Sc source is Sc2O3 or a precursor material that can be heated and decomposed to obtain Sc2O3 at a temperature not higher than the sintering temperature; The In source is In2O3 or a precursor material that can be heated and decomposed to obtain In2O3 at a temperature not higher than the sintering temperature; The Yb source is Yb2O3 or a precursor material that can be heated and decomposed to obtain Yb2O3 at a temperature not higher than the sintering temperature; The Y source is Y2O3 or a precursor material that can be heated and decomposed to obtain Y2O3 at a temperature not higher than the sintering temperature; The Er source is Er2O3 or a precursor material that can be heated and decomposed at a temperature not higher than the sintering temperature to obtain Er2O3; The Mo source is MoO3 or a precursor material that can be heated and decomposed at a temperature not higher than the sintering temperature to obtain MoO3.

3. The method for preparing a high entropy negative thermal expansion luminescent material according to claim 2, characterized in that: After Al source, Sc source, In source, Yb source, Y source, Er source and Mo source are weighed in proportion and ground and mixed evenly, the obtained mixed powder is first pre-sintered directly or pre-sintered after tableting, and then the pre-sintered product is ground and mixed evenly, and then secondary sintered after tableting; the pre-sintering temperature is 700-800°C and the time is 5-10h, and the secondary sintering temperature is 1000-1100°C and the time is 5-10h.

4. The method for preparing a high entropy negative thermal expansion luminescent material according to claim 2 or 3, characterized in that: When Al source, Sc source, In source, Yb source, Y source, Er source and Mo source are weighed in proportion and ground and mixed evenly, wet grinding is adopted. Ethanol is added during grinding, and the added amount is based on wetting Al source, Sc source, In source, Yb source, Y source, Er source and Mo source.

5. The method for preparing a high entropy negative thermal expansion luminescent material according to claim 3, characterized in that: When the pre-sintered product is ground and mixed uniformly, dry grinding is adopted.

6. The method for preparing a high entropy negative thermal expansion luminescent material according to claim 2 or 3, characterized in that: The purity of Al source, Sc source, In source, Yb source, Y source, Er source and Mo source is 99~99.99wt%.

7. The method for preparing a high entropy negative thermal expansion luminescent material according to claim 2 or 3, characterized in that: For all sintering processes involved, the temperature was raised to the sintering temperature at a heating rate of 3 to 10 °C / min.

8. The method for preparing a high entropy negative thermal expansion luminescent material according to claim 2 or 3, characterized in that: All tablets involved are pressed into cylindrical blanks with a diameter of 8~10mm and a height of 3~6mm.

9. The method for preparing a high entropy negative thermal expansion luminescent material according to claim 2 or 3, characterized in that: For all tablet pressing processes involved, the tablet pressing pressure is 4~10MPa and the pressure holding time is 2~5min.

Citation Information

Patent Citations

  • Erbium-ytterbium co-doped scandium molybdate heat-enhanced up-conversion and down-conversion luminescent material and preparation method thereof

    CN111778025A

  • Abnormal heat enhanced erbium-ytterbium co-doped molybdate luminescent material and preparation method thereof

    CN118546679A

  • Materials with low or negative thermal expansion

    US5919720A